A case study on the assessment of RF switch and splitter options for coupling of transceiver modules to bidirectional antennas employed in linear wireless sensor networks. Issue 11 (1st July 2021) - Dalveren, Yaser; Durukan, Ahmet Mert; Kara, Ali
Abstract: Recently, a concept of linear wireless sensor networks (LWSNs) has attracted much attention. For such networks, one of the key challenges in sensor node design is to couple transceiver modules with bidirectional antennas placed back‐to‐back for opposite radiation. As is known, simply, this can be achieved by using well‐known coupling options like radio frequency (RF) switch or splitter. However, it is important to decide between two seemingly equally good options according to the system requirements such as RF performance, power consumption, and cost. Therefore, this study aims to comparatively assess these options from the system level point of view to find out what advantages or disadvantages either provides as per the other from widespread use of them in a LWSN‐based cathodic protection monitoring of oil and natural gas pipelines in extreme environments. Preliminary field tests are also conducted to validate the efficiency of coupling options for LWSN links. Results show that RF splitter offers low power consumption and cost whereas RF switch has advantages of low loss. Thus, it is believed that this study may provide useful insights to design bidirectional sensor links for LWSNs.